Biologie De La Reproduction Du Sciaenidae Pseudotolithus Elongatus Dans La Lagune Ebrie (Cote d’Ivoire) - Koné Tiéhoua; Kouakou Fokouo Kessia Irène; Konan Kouassi Sylvain; N’Da Konan (European Scientific Journal, ESJ, 2016)
The study of reproduction of Pseudotolithus elongatus in the Ebrie lagoon was investigated between July 2013 and June 2015 on a whole of individuals of 550 specimens. the total length ranges from 14.5 to 42.7 cm. The monthly evolution of the gonado-somatic index (GSI), the liver-somatic index (LSI), the condition factor (K), the Sex-ratio, the fecundity, the diameter of eggs revealed that this species spawns throughout the year but the main breeding period was in raining season. Sex-ratio observed was in favour of females (1: 1. 14; X2 = 2.26; p > 0.05). The percentage of mature specimens by sexes was calculated for each size class. Total length at first maturity was 21.06 cm for females and 20.21cm for males. The ripe ovaries contained 39883-814757 eggs. The relative fecundity was 216-1979 eggs per g of body weight of females. And the mean diameter of eggs is 336 ±138 microns.